Peter Carey - Woodcock, Bruce (Contemporary world writers., 2003)
Peter Carey is one of the most respected novelists currently writing. Since the original edition of this book, Carey's fiction has reached a far wider international audience: he has won the Booker Prize for the second time with True History of the Kelly Gang, while Oscar and Lucinda has been made into a successful feature film. Bruce Woodcock's revised and expanded critical study now includes detailed readings of the recent novels, Jack Maggs and True History of the Kelly Gang, seeing them as the finest productions of a writer who continues to surprise and delight his readers with inventive creations and unique imagination. The book explores Carey's position not only as a great entertainer but also as a disturbing postcolonial writer, setting his work in relation to his life and influences. Using previously neglected radio interviews amongst other documents, Woodcock sees Carey as a fictional shadow maker, whose characters often inhabit the unpredictable borderlands of experience. Commenting on the novels' fabulist, surrealist and postmodernist elements, Woodcock also stresses the political concerns of Carey's work, and presents him as a syncretic writer who relishes the diversity of his varied imaginings and his own capacity to take risks with his fiction. Woodcock provides both students and the general reader with detailed examinations of all Carey's major works as well as a survey of critical debates, in this most accessible and involving account.